(untitled) (American Journal of Islam and Society, 2013)
The Persian Gulf region is home to the six members of the Gulf Cooperation Council (viz., Oman, the UAE, Qatar, Bahrain, Kuwait, and Saudi Arabia), Iran, and Iraq. Holding over 60 percent of the world’s oil and over 40 percent of its natural gas reserves, the Persian Gulf is central to the global economy. Yet a dominant regional power is lacking; beginning with the British in the late nineteenth century, foreign powers have consistently been meddling in the region. Significant economic, social, cultural, and political changes have transformed the region’s international relations since Britain’s withdrawal in the 1960s. The contributors to this volume, which provides a rich account of this transformation, focus on natural resources, the Iranian-Saudi competition, the interest of major external actors, and political reform. The volume’s main thrust is the centrality of both state and regime security in order to understand the region. The volume’s editor, Mehran Kamrava, notes that the international politics there is essentially that of security politics. He offers four reasons for this: (1) its central role in oil and natural gas production and, increasingly, global finance, (2) the competition between Iran and Saudi Arabia over regional leadership, (3) the long-standing American-Iranian conflict, and (4) the instability brought about by intermixing politics and religion. He identifies three poles of power that shape the region’s security dynamics: the American pole; the GCC pole, which is centered on Saudi military and Qatari-UAE financial power; and the Iranian pole, which relies both on military might and soft power. Since the Iranian revolution, the American and the GCC poles have built a resilient alliance that has been driven by both the United States’ growing direct involvement and the GCC’s failure to provide security to its members. The chapters, written by leading regional specialists, further elaborate on the region’s security dynamics. In Chapter 2, J. E. Petersen offers a useful typology of boundary formation. He discusses how the state-building process, historical claims, colonial imposition, and resource competition have shaped state boundaries. As these boundaries remain contested, Petersen details various ongoing problems. In Chapter 3, Fred H. Lawson refines the concepts “security dilemma” and “alliances dilemma” and uses them to explain the arms race in the Gulf since the first Gulf War. Middle East specialists and international relations scholars will find these chapters useful in conceptual refinement ...